2013
DOI: 10.1002/ejic.201201233
|View full text |Cite
|
Sign up to set email alerts
|

N‐Methyl‐4,4′‐bipyridinium and N‐Methyl‐N′‐oxide‐4,4′‐bipyridinium Bismuth Complexes – Photochromism and Photoluminescence in the Solid State

Abstract: Three bismuth complexes based on N-methyl-4,4Ј-bipyridinium (hMV + ), (hMV)[Bi(hMV)Cl 5 ] (1), and N-methyl-NЈ-oxide-4,4Ј-bipyridinium (MVO + ), [Bi(MVO)X 4 (dmso)]·dmso [X = Cl (2), Br (3)], are reported. All three compounds show luminescence in the solid state with maxima at 545 nm (yellow for 1) and 560 nm (orange for 2 and 3) with quantum yields [a]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(28 citation statements)
references
References 44 publications
2
26
0
Order By: Relevance
“…Therefore, it can be concluded that dehydration of 1 and 2 strongly increases the intensity of luminescence. Interestingly, the intensity is generally higher for the chloride complexes then for the bromides, and this observation completely agrees with those made by Mercier et al for viologen-based complexes ("this clearly shows that changing the halide has an influence only on the luminescence intensity") 11 . Probably, there is no general correlation applicable for the whole panoply of polynuclear Bi(III) halides, but it may appear in some particular cases.…”
Section: Resultssupporting
confidence: 91%
“…Therefore, it can be concluded that dehydration of 1 and 2 strongly increases the intensity of luminescence. Interestingly, the intensity is generally higher for the chloride complexes then for the bromides, and this observation completely agrees with those made by Mercier et al for viologen-based complexes ("this clearly shows that changing the halide has an influence only on the luminescence intensity") 11 . Probably, there is no general correlation applicable for the whole panoply of polynuclear Bi(III) halides, but it may appear in some particular cases.…”
Section: Resultssupporting
confidence: 91%
“…From the point of view of inorganic synthesis, the obtained data clearly confirm previously made observations that the use of HX acids as a source of halide anion and a reaction medium promotes the formations of low-nuclear complexes with higher X/Bi ratio. Besides, the luminescence data are in very good agreement with those found by Mercier et al for other chloro-and bromobismuthate hybrids: ''this clearly shows that changing the halide has an influence only on the luminescence intensity'' [15], so this feature of Bi (III) halide complexes seems so be rather common, although the difference between 1 and 2 is more dramatic than those found earlier.…”
Section: Discussionsupporting
confidence: 85%
“…Moreover, these properties may be tuned by changing the substituents at the N site [12][13][14]. Theoretical models of the observed effects have been also put forward [15]. However, almost all these studies are still focused on the 4,4-bipyridine ''core'' in the cations.…”
Section: Introductionmentioning
confidence: 99%
“…[38] Thus achieving phosphorescence by incorporation of this element into molecules is of great interest for various applications, such as in OLEDs and in bioimaging. [40] (44). [40] (44).…”
Section: Bismuth and Antimonymentioning
confidence: 99%